Isolated unilateral hypoglossal nerve paralysis: a report of two cases [Tek tarafli izole hipoglossal sinir paralizisi: iki olgu sunumu.] - (:unkn) unknown (My University, 2003)
Two cases of unilateral isolated hypoglossal nerve paralysis are presented. One patient (aged 56 years, male) had a history of intubation during open cardiac surgery. Spontaneous clinical improvement was observed about 3.5 months after the onset of paralysis. In the other patient (aged 42 years, female), the onset of paralysis dated back 23 years before. Since no etiologic cause could be determined to be associated with hypoglossal nerve paralysis either at the time of onset or on final examinations, the case was thought to be idiopathic. No clinical improvement was observed during a six-month follow-up period.